1980
DOI: 10.1159/000308974
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of the Corneal Epithelium after Application of Topical Anaesthetic Ointments

Abstract: The effect of topical anaesthetic ointments (4% cocaine, 4% xylocaine, 0.5% proparacaine, 0.2% oxybuprocaine) on the corneal epithelium of rabbits was examined using a scanning electron microscope. Even after a single application, the more toxic effect of cocaine compared to the other topical anaesthetics was evident. Cocaine caused disruption of both the plasma membrane and the cytoplasm. After a single application, the other preparations caused a marked decrease in the microvilli and microphcae, disruption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
3

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 3 publications
(3 reference statements)
0
15
0
3
Order By: Relevance
“…19 Topical anesthetics inhibit the rate of corneal epithelial cell migration by disrupting the cytoplasmic action in filaments and destroy superficial corneal epithelial microvilli. 20 The mechanism of action of potentiating effect of proparacaine on tropicamide-induced pupillary dilation may be because of an increased intraocular penetration of tropicamide which is because of greater availability of the drug due to increased absorption through the microscopic disruptions in the corneal epithelium and reduced tearing because of which more time of contact and hence increased bioavailability might have been achieved. 9,13,16,21,22 …”
Section: Discussionmentioning
confidence: 99%
“…19 Topical anesthetics inhibit the rate of corneal epithelial cell migration by disrupting the cytoplasmic action in filaments and destroy superficial corneal epithelial microvilli. 20 The mechanism of action of potentiating effect of proparacaine on tropicamide-induced pupillary dilation may be because of an increased intraocular penetration of tropicamide which is because of greater availability of the drug due to increased absorption through the microscopic disruptions in the corneal epithelium and reduced tearing because of which more time of contact and hence increased bioavailability might have been achieved. 9,13,16,21,22 …”
Section: Discussionmentioning
confidence: 99%
“…14 This results in morphologic changes of the epithelial cells, with desquamation that manifests as loosening of the epithelium. 15 Renewal of the epithelial layer is subsequently observed with the formation of tighter cellular adhesion, preventing recurrence of erosions. 16 Dua et al 17 used alcohol delamination for the management of recurrent erosions.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopic studies on rat and rabbit corneas have demonstrated that corneal changes can occur following normal usage of anaesthetics, even with a single application of topical anaesthetic 19. Brewitt et al 20 reported morphological changes in rabbit corneal epithelial cells after a single application of ointment formulations of proxymetacaine (0.5%) and oxybuprocaine (0.2%). Wilson et al 21 showed a significant increase in epithelial cell sloughing for 6 hours after a single application of proxymetacaine (0.5%).…”
Section: Discussionmentioning
confidence: 99%